2016
DOI: 10.1111/aas.12716
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetists stress is induced by patient ASA grade and may impair non‐technical skills during intubation

Abstract: Background The aims of this study were to determine if patient ASA grade was associated with increased stress in anaesthetists with a subsequent effect on non‐technical skills. Methods Stress was measured using a validated objective (heart rate variability or heart rate) and subjective tool. We studied eight consultant anaesthetists at baseline (rest) and during 16 episodes of intubation with an ASA 1 or 2 patient vs. an ASA 3 or 4 patient. The primary outcome for the study was objective and subjective stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…HRV has been previously been well correlated with STAI by our group in consultant surgeons performing elective colorectal resections (Jones et al 2015) and in consultant anaesthetists during intubation (Doleman et al 2016), but this study suggests that this may not be the case in the simulated environment. Given that 6/8 participants identified their most physiologically stressful step correctly in the theatre environment (vs 1/8 in the simulated environment), it would appear that participants are less in tune with physiological changes that occur with stress when in an unfamiliar environment.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…HRV has been previously been well correlated with STAI by our group in consultant surgeons performing elective colorectal resections (Jones et al 2015) and in consultant anaesthetists during intubation (Doleman et al 2016), but this study suggests that this may not be the case in the simulated environment. Given that 6/8 participants identified their most physiologically stressful step correctly in the theatre environment (vs 1/8 in the simulated environment), it would appear that participants are less in tune with physiological changes that occur with stress when in an unfamiliar environment.…”
Section: Discussionmentioning
confidence: 56%
“…Our finding that simulation was unable to recreate the stress of performing the technical procedure has implications for the ability of SBT to contribute towards the mastery of clinical procedures in trainee clinicians. Stress may have positive (Smeets et al 2009) or negative effects (Harvey et al 2012) upon learning, and is known to have a detrimental effect on both technical ) and non-technical skills (Doleman et al 2016). SBT is frequently used to assess these domains in medical education and the research arena (Yee et al 2005); therefore the validity of such assessments and the application of findings from research studies in the simulated environment to clinical practice may be questioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These risk factors included age, sex, hypertension, coronary heart disease, peripheral vascular disease, haemoglobin, duration of surgery, magnitude of surgery, general anaesthesia, blood loss, medication use (ACE inhibitors, β-blockers, calcium antagonists and diuretics), eGFR, intensive care unit (ICU) stay, and American Society of Anesthesiologists (ASA) grade [13]. We reported adjusted odds ratios and associated 95% CIs and p values.…”
Section: Methodsmentioning
confidence: 99%
“…The first choice starts at this moment, what FiO 2 should one use? One hundred percent is a very attractive choice since, a very good reserve will allow some time for laryngoscopy and intubation, and we all know this is a quite thrilled moment [5], nevertheless there is a price for this relief. Atelectasis are prone to develop with the choice of preoxygenation with 100% FiO 2 [3], and this is a major issue, that needs a special intervention, namely the use of positive end expiratory pressure (PEEP) to maintain the lungs open [3], since even recent investigation have shown that if this is not instituted to the patient, the lung will certainly be poorly aerated [6].…”
Section: Oxygenmentioning
confidence: 99%